The effect of malting on phenolic compounds and radical scavenging activity in grains and breakfast cereals. Issue 9 (23rd August 2022) - Vingrys, Kristina; Mathai, Michael; Ashton, John F.; Stojanovska, Lily; Vasiljevic, Todor; McAinch, Andrew J.; Donkor, Osaana N.
Abstract : Abstract: Breakfast cereals are popular grain foods and sources of polyphenols. Malting alters polyphenol content and activity; however, effects are varied. The total polyphenol content (TPC), radical scavenging activity (RSA), and polyphenol profile were analyzed in unmalted and malted grains (wheat, barley, and sorghum) and breakfast cereals (wheat, barley) by Folin Ciocalteu Reagent (FCR), % inhibition of the free radical 2, 2‐diphenyl‐1‐picryl‐hydrazyl, and high performance liquid chromatography. Higher TPC was observed in all malted grains and breakfast cereals compared with unmalted samples ( p  < 0.05). Higher RSA was also observed in all malted samples compared to unmalted samples ( p  < 0.05) except for wheat grain to malted wheat grain. In this study, malting induced additional polyphenols and antioxidant activity in grains and cereal products. Malted grain breakfast cereals may be practical sources of polyphenol antioxidants. Practical Application: This study utilized malting in a unique way to investigate potential health benefits of polyphenols and antioxidant activity in grains (wheat, barley, and sorghum) and ready‐to‐eat breakfast cereals (wheat and barley). This study found that grains and breakfast cereals are important sources of antioxidant polyphenols, and these were significantly increased in malted varieties. Understanding this is important as grains and breakfast cereals are widely consumed staple foods. Consuming healthier grain products may be a practical strategy in reducing the risk of noncommunicable diseases such as colorectal cancer and type‐2 diabetes, where wholegrain consumption may be important in prevention.